Distinct lower respiratory tract microbiota profiles linked to airway mucus hypersecretion in children with Mycoplasma pneumoniae pneumonia - Wei, Xiwen; Wang, Wan; Cheng, Hang; Huang, Yin; Zhou, Qixian; Yuan, Xiaopeng (Frontiers in Microbiology, 2024)
Background: Airway mucus hypersecretion (AMH) can occur in children with acute respiratory diseases, but its underlying mechanisms and relationship with the lower respiratory tract microbiota (LRTM) are not yet fully understood. This study investigates the characteristics of LRTM in children with Mycoplasma pneumoniae pneumonia (MPP) and its impact on AMH. Methods: We collected bronchoalveolar lavage fluid and related clinical indicators from 202 children with MPP. 16S rRNA gene amplicon sequencing was used for detection and identification. Microbial diversity and characteristic genera were compared, and their abundance was analyzed for correlations with clinical factors. Results: As the disease course (days from onset to bronchoscopy, grouped into T1, T2, T3) extended, α-diversity of the LRTM gradually increases, particularly in the T3 hypersecretion group. Moreover, significant differences were observed in the incidence of AMH, co-infection rates, peripheral white blood cell (WBC) count, and C-reactive protein levels. In AMH, Mycoplasmoides and Veillonella abundance and peripheral neutrophils are risk factors for increased secretions. In addition, in the T3 co-infection group, Streptococcus and Prevotella increased, replacing Stenotrophomonas as the dominant genus, possibly due to β-lactam antibiotic use. Prevotella abundance was strongly correlated with WBC.The composition and structure of LRTM in children with MPP plays a crucial role in AMH and disease progression.